Pembekalan Teknologi Informasi Untuk Menyongsong Era Industri 4.0 Pada Siswa SMK Muhammadiyah Piyungan - Sudarmana, Landung; Rahmawati, Titik; Priyanto, Agung (DHARMA BAKTI, 2022)
Indonesia is facing the Industrial Revolution 4.0, an era where technologicaldevelopments are applied to various aspects, including manufacturing with artificialintelligence (AI) support which is also supported by internet of things (IoT) technology,human-machine interfaces, robotic and sensor technology, and three-dimensional (3D)printing technology that supports the industry. Changes in the world of work that areinfluenced by the Industrial Revolution 4.0 are challenges for Vocational High School(SMK) graduates. This is because many fields of work that have been filled with human laborhave been replaced by technology, machines, robots, or artificial intelligence. As a result,many graduates who should be able to work immediately are threatened to be unemployed.Efforts to be able to compete in the Industrial Revolution, educational institutions playan important role. They must be able to equip their students the abilities to keep up withchanges that occur quickly. As an anticipation, SMK Muhammadiyah Piyungan held abriefing activity with a face-to-face lecture methodology so that there was an interactivebetween students and the presenters.The results of this community service are expected to provide provisions for studentsto become competent and ready to work in that era. For institutions, the results are expectedto provide inputs, in the form of overviews, to the curriculum makers in accordance with theIndustrial Revolution era